Abanindranath Tagore / his early work - Tagore, Abanindranath. 1871-1951.; Chakravorty, Ramendra Nath, 1902-1955. (Calcutta : Art Section, Indian Museum ; Distributors, Visva Bharati, 1951)
Reproduction of paintings of a Bengali school of painter; includes critical introduction.
Microfilm.
Keywords: Tagore, Abanindranath, -- 1871-1951.; Painting, Bengali